[Date Index] [Thread Index] [Author Index]
Re: Re: Simplifying constants...bug?
Alan, This is done using version 4; however, I believe the results will be the same in version 3. (a + c*d)/(c*d) //. c*d -> -z (a - z)/(c*d) FullForm[%] Times[Power[c, -1], Power[d, -1], Plus[a, Times[-1, z]]] Note that the FullForm does not include the product c*d. Ingeneral, I find that it works better to structure a replacement such that a single variable rather than an expression is being replaced. (a + c*d)/(b + c*d) //. c -> -z /d (a - z)/(b - z) (a + c*d)/(c*d) //. c -> -z/d -((a - z)/z) Bob Hanlon In a message dated 7/10/99 8:40:24 AM, calvitti at boes.ces.cwru.edu writes: >here's some intersting behavior in 3.0: > > (a + c*d)/(b + c*d) //. c*d -> -z > >gives (as expected): > > (a - z)/(b - z) > >yet > > (a + c*d)/(c*d) //. c*d -> -z > >no longer simplifes the denominator: > > (a+b-z)/(c*d) > >anyone know why? >